Growth performance of paraserianthes falcataria (batai) planted in bioplastic pots title - Liew, Kang Chiang; Chang, Chui Yee; Julius Kodoh; Russel@ Andy Immit Mojiol; Crispin Kitingan (Zes Rokman Resources, 2016)
Paraserianthes falcataria, a fast growing tree species was evaluated for 180 days planted in bioplastic pots. Six different ratios of newspaper and bioplastic mixture (N100:B0, N90:B10, N70:B30, N50:B50, N30:B70 and N10:B90) were used for pot making. The heights of the seedlings were measured together with root penetrations through the bioplastic pots at the end of evaluation period. Results showed that the seedlings planted in 100% fully newspaper pot had the highest percentage of mean height 4964.94% meanwhile the N30:B70 had the lowest percentage of height 4396.65%. No significant difference between the height and the ratio of bioplastic mixing at the p≤0.05 for the seedlings and negative impact to the plant growth. From the observation also, the number of seedling roots penetrated through the bioplastic pots were more than 10 roots where the root systems were able to break through the pot wall.